This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Same way man!!!
If u take square of both term and then solve it, it gives "i" answer...
Log in to reply
Huh? This is not a 'solve it' question it is a quasi 'simplify' question - rewrite the expression in simplest form with a real denominator. btw - if you square the expression the numerator is -2i and the denominator is 2i so the square of the expression is -1. That is what one gets as (-i)^2 = -1. Nice explanation Nihar.
If we let "?" = X.... Multiply both "sides" by 1+i and get:
1 - i = X + iX
Square both "sides" and get:
(1 - i)(1 - i) = (X + iX)(X + iX)
1 - 2i + i^2 = X^2 + 2iX^2 + (i^2)(X^2)
1 - 2i - 1 = X^2 + 2iX^2 - X^2
-2i = 2iX^2
Divide both "sides" by 2i:
-1 = X^2
X = sqrt(-1)
X = ?, so
X = i
Can someone please explain how this is incorrect? Thanks in advance!
Log in to reply
I did this. Why my result isnt the same?
(1-i)/(1+i)=a
((1-i)^2)/((1+i)^2)=a^2
(1-2i+i^2)/(1+2i+i^2)=a^2
(1-2i-1)/(1+2i-1)=a^2
(-2i)/(2i)=a^2
-1=a^2
a=sqrt(-1)=i PD: Please excuse the test format. :D
When you take the square root of a number, here − 1 , you have to remember that there's a positive AND negative solution: X 2 = − 1 ↔ X = ± − 1
Shit man by mistakely selected a wrong option! :'(
I got 1/i, which is I because I multiplied top & bottom by (1+i)
Multiplying both sides by the conjugate of the denominator works. But here is another cute solution:
Note that 1 = − i 2 . Then z = 1 + i 1 − i = 1 + i − i − i 2 = 1 + i ( − i ) ( 1 + i ) = − i .
Or, draw 1 − i and 1 + i as points in the complex plane and connect them to the origin. It is easy to see that from 1 + i to 1 − i requires a rotation of 9 0 ∘ anti-clockwise, without changing the length. This is precisely what multiplication by − i does. Therefore, z = − i .
Nice solution!
That was simple.
Everyone knows that i 2 = − 1 .
Now,
1 + i 1 − i = ( 1 + i ) ( 1 − i ) ( 1 − i ) 2 = 1 − i 2 1 − 2 i + i 2 = 1 − ( − 1 ) 1 − 2 i − 1 = 1 + 1 − 2 i = 2 − 2 i = − i
Problem Loading...
Note Loading...
Set Loading...
1 + i 1 − i = ( 1 + i ) ( 1 − i ) ( 1 − i ) 2 = 1 − i 2 1 − 2 i + i 2 = 1 − ( − 1 ) 1 − 2 i − 1 = 1 + 1 − 2 i = 2 − 2 i = − i